"Agro biodiversidad genética intra-especifica de frejol voluble (Phaseolus vulgaris L.) en el cantón saraguro, alternativa de manejo ambiental sostenible": - Coronel Becerra, Jorge Wilson (2010)
The main purpose of this research project is to generate information and knowledge that allows to contribute to the cultivation of voluble beans Phaseolus vulgaris L. in the population of Saraguro, Tenta and Celén parishes present less vulnerability to pest attack, through the increase in the use of genetic diversity on the farm, which in turn allows increasing the yields per unit area, preserve food security, genetic diversity and improve preservation of ecosystem health. This is achieves by providing farmers and researchers with tools and practices to manage the intra-specific diversity of the local crop. After the execution of the field work and the statistical analysis carried out at the present thesis work, the following information is available: The use of biodiverse mixtures in plantings of voluble beans in fields of small farmers, guarantees better yields at the level of small producer. The productive, agronomic, phenotypic, and sanitary behavior of mixtures or mixtures of biodiversity and individual populations. A collection of selected ecotypes of voluble beans is available made up of 25 ecotypes or varieties with agronomic characteristics, sanitary and of superior quality to the mixed ones currently cultivated. Information is available on the causes of genetic erosion of the germplasm of fickle beans grown in the fields of parish growers in study. The health and performance performance of the mixes and of the individual populations of voluble beans analyzed and it is known which are the top. The high yields that are achieved with the cultivation of biodiverse mixtures of voluble beans in the canton Saraguro, generate greater economic profit than those obtained with the monoculture sowing of Canarian beans, variety preferably in the market, especially when these are marketed in tender state....................................................................................................................................................